2004
DOI: 10.1080/14620316.2004.11511785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spring soil nitrogen application on nitrogen remobilization, uptake, and partitioning for new growth in almond nursery plants

Abstract: SUMMARYOne year old 'Nonpareil' almond (Prunus dulcis (Mill) D. A. Webb) trees on 'Lovell' rootstocks were used to evaluate the effects of soil nitrogen (N) availability in the spring on N remobilization, uptake, partitioning, and tree growth. After being transplanted to an N-free medium, the trees received a modified Hoagland solution, with or without N from 15 N-depleted NH 4 NO 3 , twice a week for 12 weeks. During the first four weeks, the N used for new shoot and leaf growth mainly came from the nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Nevertheless, nursery is a peculiar growth environment characterised by: i) sandy and poorly structured soils to limit root damages during mechanical tree removal; ii) ultra-high planting density (often >40.000 trees ha -1 ) to best use soil surface and optimise the agronomic management (irrigation, fertilisation, pest and diseases control); iii) high competition among tree roots as a consequence of the high planting density and soil texture. As outcome, nursery trees are more dependent on the mineral uptake than mature trees because of their smaller root size, limited storage reservoirs and reduced vegetative growth (Bi et al, 2004). Therefore, with the aim to promote a fast growth, generous fertilisation rates and irrigation volumes are sometimes adopted (Castle and Rouse, 1990) in commercial nurseries.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, nursery is a peculiar growth environment characterised by: i) sandy and poorly structured soils to limit root damages during mechanical tree removal; ii) ultra-high planting density (often >40.000 trees ha -1 ) to best use soil surface and optimise the agronomic management (irrigation, fertilisation, pest and diseases control); iii) high competition among tree roots as a consequence of the high planting density and soil texture. As outcome, nursery trees are more dependent on the mineral uptake than mature trees because of their smaller root size, limited storage reservoirs and reduced vegetative growth (Bi et al, 2004). Therefore, with the aim to promote a fast growth, generous fertilisation rates and irrigation volumes are sometimes adopted (Castle and Rouse, 1990) in commercial nurseries.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of conifers (Meyer and Splittstoesser, 1971;Millard and Proe, 1993;Nambiar and Fife, 1991) and deciduous plants (Bi et al, 2004;Deng et al, 1989;Millard and Neilsen, 1989) have demonstrated that nitrogen applied during the previous year can strongly affect growth the next year. Poor mineral nutrition while holding trees in a mulch bed may contribute to a reduction in establishment and growth of trees during the first year or more after transplanting.…”
mentioning
confidence: 99%